2019
DOI: 10.3892/etm.2019.7776
|View full text |Cite
|
Sign up to set email alerts
|

Ropivacaine vs. levobupivacaine: Analgesic effect of combined spinal‑epidural anesthesia during childbirth and effects on neonatal Apgar scores, as well as maternal vital signs

Abstract: The present study aimed to investigate and compare the analgesic effect and safety of ropivacaine or levobupivacaine in combined spinal-epidural anesthesia during childbirth and their effects on neonatal Apgar scores, as well as maternal and neonatal vital signs. A total of 615 maternal patients undergoing labor between April 2016 and March 2017 were divided into two groups according to the analgesic used for combined spinal-epidural anesthesia during childbirth: The ropivacaine group (n=318) and the levobupiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, ropivacaine had a faster onset and less effect on maternal vital signs for anesthesia in delivery compared to levobupivacaine and was associated with a decrease in maternal the cesarean section rate among patients who did not initially choose a cesarean section. Therefore, it is useful in clinical practice (23). Evaluating ropivacaine and bupivacaine in cesarean section anesthesia, it was observed that ropivacaine had a little effect on hemodynamic indices (including blood pressure and heart rate) with a decreasing effect on the duration of sensory and motor block.…”
Section: Discussionmentioning
confidence: 99%
“…However, ropivacaine had a faster onset and less effect on maternal vital signs for anesthesia in delivery compared to levobupivacaine and was associated with a decrease in maternal the cesarean section rate among patients who did not initially choose a cesarean section. Therefore, it is useful in clinical practice (23). Evaluating ropivacaine and bupivacaine in cesarean section anesthesia, it was observed that ropivacaine had a little effect on hemodynamic indices (including blood pressure and heart rate) with a decreasing effect on the duration of sensory and motor block.…”
Section: Discussionmentioning
confidence: 99%
“…Ropivacaine is believed to exert selective effects on sensory fibers, has a stronger ability to inhibit nerve conduction in pain-sensitive fibers, and exhibits less mobility reduction [28,29]. Levobupivacaine is a bupivacaine S(−) isomer that has an onset and duration of action similar to bupivacaine, but with fewer toxic effects on the cardiovascular and central nervous systems [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Levobupivacaine is a bupivacaine S(−) isomer that has an onset and duration of action similar to bupivacaine, but with fewer toxic effects on the cardiovascular and central nervous systems [30,31]. Although levobupivacaine may have a slower onset, it exerts higher motor block than ropivacaine [29]. The combination of local anesthetics may influence the painrelieving effect or morphine and, thus, indirectly moderated the occurrence of pruritus.…”
Section: Discussionmentioning
confidence: 99%
“…Cesarean section is one of the most common surgeries in obstetrics, the rate of which is increasing significantly worldwide (1)(2)(3)(4). The rate of cesarean section has been reported at 42.35% in the world and 47.9% in Iran (5,6). The correct management of delivery and choosing the appropriate anesthetic method to achieve analgesia and maintain the health of the mother and fetus during cesarean section are of great importance (7).…”
Section: Contextmentioning
confidence: 99%